2009
DOI: 10.1891/0047-2220.40.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Employment Outcome Rates of African American Versus White Consumers of Vocational Rehabilitation Services: A Meta-Analysis

Abstract: This research examined the relationship between race/ethnicity and rehabilitation outcomes as measured by closure status for VR consumers across two different target populations: persons with mental retardation and those who are deaf/hard-of-hearing. The researchers employed a meta-analysis to test the association between the predictor and criterion variables using select Rehabilitation Services Administration (RSA-911) driven studies. Data analyzed represent consumer case file information collected during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…work collaboratively with a diverse group of individuals” (CRCC, 2017, p. 1). Discussions emerged among the task force members surrounding racial and ethnic health disparities concerning the gaps in services and trends of vocational outcomes for diverse consumers (Matrone & Leahy, 2005; Moore et al, 2009; Wilson, 2002). Discussions about such inequities in our backyard inspired the development of a new section of the Code that seeks to transform multicultural competencies (Arredondo et al, 1996; Atkins, 1988; Middleton et al, 2000) into enforceable standards of practice for all counselors to uphold.…”
Section: Historical Perspectives and Milestonesmentioning
confidence: 99%
See 1 more Smart Citation
“…work collaboratively with a diverse group of individuals” (CRCC, 2017, p. 1). Discussions emerged among the task force members surrounding racial and ethnic health disparities concerning the gaps in services and trends of vocational outcomes for diverse consumers (Matrone & Leahy, 2005; Moore et al, 2009; Wilson, 2002). Discussions about such inequities in our backyard inspired the development of a new section of the Code that seeks to transform multicultural competencies (Arredondo et al, 1996; Atkins, 1988; Middleton et al, 2000) into enforceable standards of practice for all counselors to uphold.…”
Section: Historical Perspectives and Milestonesmentioning
confidence: 99%
“…Discussions about such inequities in our backyard inspired the development of a new section of the Code that seeks to transform multicultural competencies (Arredondo et al, 1996; Atkins, 1988; Middleton et al, 2000) into enforceable standards of practice for all counselors to uphold. Decreasing the racial and ethnic disparities across acceptance, service provision, closure types, and employment outcomes (Moore et al, 2009; Wilson et al, 2001; Wilson, 2002) was a vital element of focus throughout the revision of the ethics code. The new section, along with overall revisions to the ethics code, has been generated to hold rehabilitation counselors accountable for the ongoing gaps in services to many underserved groups.…”
Section: Historical Perspectives and Milestonesmentioning
confidence: 99%
“…Employment and health disparities are intensified for individuals with multiple intersecting identities (e.g., race/ethnicity, gender, disability, and poverty) who are at risk for experiencing high levels of stigma, unconscious bias, health issues, and employment difficulties (Purdie-Vaughns & Eibach, 2008; Shaw et al, 2012; Vera et al, 2018). Rehabilitation researchers have suggested that racial biases were at least in part responsible for the inequitable patterns of VR service delivery for African Americans and other racial and ethnic minority clients (McGinn et al, 1994; Rosenthal et al, 2005; Wilson et al, 2001; Wilson & Senices, 2005).…”
mentioning
confidence: 99%
“…The VR program is not free from bias and can influence service provision and outcomes for PWDs. Studies have reported racialized differences in VR acceptance rates (Rosenthal et al, 2005) and service provision (Wilson et al, 2002). Specifically, White VR consumers were 80% to 91% more likely to be closed in self-employment, whereas female VR consumers were 26% to 30% less likely to be closed in self-employment (Yamamoto & Alverson, 2013, 2017).…”
mentioning
confidence: 99%